Solução de comunicação sem fio em frequência sub-GHz baseada em LPWA para IoT - Carvalho, Giselle Braga (2019)
This project has developed a wireless communication solution for sub-GHz operation in the frequency band licensed in 250 MHz based on LPWA technology for the internet of things applied in smart cities using simulations with RF coverage prediction tools known as Radio Mobile and CelPlanner and IPv6 data network known as Packet Tracer and has proven the technical feasibility of sharing communication infrastructure in a multiservice and multiuser environment and the reduction of communication network element (base radio stations) resulting in the reduction of financial expenses with CAPEX in deployment and OPEX in the operation and maintenance of the network allowing support for a real deployment.